Exploration of Improving Teacher Competence in Teaching Indonesian Language in Junior High Schools in Rural Areas - Munawarah, Munawarah; Riskawati, Riskawati; Damayanti, Damayanti (Educia Journal, 2024)
The research analyzes the educational experiences of rural junior high school Indonesian language teachers by examining their teaching competence improvement barriers. A qualitative method enabled researchers to obtain data from classroom observations together with in-depth interviews and focus group discussions involving twelve teachers who teach at different rural educational facilities. Research demonstrates that rural teachers experience important barriers because they face restricted access to basic resources together with restricted access to professional development and technological support. Despite these obstacles, teachers employ various strategies for self-improvement, such as peer collaboration, online learning, and community support. Rural teachers receive essential help from neighborhood residents who provide facilities along with encouragement to bridge their educational deficiencies. This research demonstrates both the significance of nonformal professional support systems used by teachers as well as their ability to cope with their individual teaching situations effectively. Rural schools need both enhanced organizational backing and stronger community involvement to build teacher qualification levels which produces better academic outcomes in their areas. The study contributes to research overlooking rural education while providing concrete suggestions for authorities and education leaders to enhance teacher development in underserved rural regions.